Parents' needs and perceived gaps in communication with healthcare professionals in the neonatal (intensive) care unit: A qualitative interview study. Issue 7 (July 2021) - Lorié, Esther S.; Wreesmann, Willem-jan W.; van Veenendaal, Nicole R.; van Kempen, Anne A.M.W.; Labrie, Nanon H.M.
Highlights: Adequate parent-provider interaction is pivotal to support family-integrated care. Four distinct functions of parent-provider communication can be distinguished. There are persisting gaps in parent-provider communication in the NICU. Gaps include the lack of written and emotional support, and the disregard of parents' views. NICU staff education should include a focus on parent-provider interaction. Abstract: Objective: To explore parents' needs and perceived gaps concerning communication with healthcare professionals during their preterm infants' admission to the neonatal (intensive) care unit (NICU) after birth. Methods: Semi-structured, retrospective interviews with 20 parents of preterm infants (March 2020), admitted to a Dutch NICU (level 2–4) minimally one week, one to five years prior. The interview guide was developed using Epstein and Street's Framework for Patient-Centered Communication. Online interviews were audio-taped and transcribed verbatim. Deductive and inductive thematic analysis was performed by two independent coders. Results: Communication needs and gaps emerged across four main functions of NICU communication: Building/maintaining relationships, exchanging information, (sharing) decision-making, and enabling parent self-management. Communication gaps included: lack of supportive physician communication, disregard of parents' views and agreements, missing communication about decisions, and the absence of written (discharge) information. Conclusion: This study improves our understanding and conceptualization of adequate NICU communication by revealing persisting gaps in parent-provider interaction. Also, this study provides a steppingstone for further integration of parents as equal partners in neonatal care and communication. Practice implications: The results are relevant to practitioners in the field of neonatal and pediatric care, providing suggestions for tangible improvements in NICU care in the Netherlands and beyond.